2020
DOI: 10.1016/j.celrep.2020.108307
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Enriched Coding and Long Non-coding RNA Genes Are Overrepresented in Recurrent Neurodevelopmental Disorder CNVs

Abstract: Highlights d We introduce SNATCNV as a tool to analyze CNV associations with genetic diseases d SNATCNV identifies 47 recurrently duplicated/deleted CNVs associated with autism d We show that CNV regions are associated with distinct sets of DECIPHER phenotypes d We provide an extensive list of brain-enriched coding and lncRNA genes

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…In the Decipher databases no patients have been reported with CNVs overlapping with the duplication, while several patients have been reported with the same deletion, many of whom present ID, one presenting with intrauterine growth retardation (IUGR) and hyperechogenic kidneys, and one presenting with diabetes. In our series of patients, ten had proximal breakpoints downstream to those presented in [44], although the brain-enriched coding and lncRNA genes are the same (respectively, four and five, Table 2, [44]). IUGR was present in one patient with deletion and in another with duplication.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the Decipher databases no patients have been reported with CNVs overlapping with the duplication, while several patients have been reported with the same deletion, many of whom present ID, one presenting with intrauterine growth retardation (IUGR) and hyperechogenic kidneys, and one presenting with diabetes. In our series of patients, ten had proximal breakpoints downstream to those presented in [44], although the brain-enriched coding and lncRNA genes are the same (respectively, four and five, Table 2, [44]). IUGR was present in one patient with deletion and in another with duplication.…”
Section: Discussionmentioning
confidence: 71%
“…A confirmation of 17q12 recurrent CNVs' strong association with neurodevelopmental disorders has been recently highlighted considering brain-enriched coding and long noncoding (lnc) RNA genes [44]. In particular, authors reported two patients: the former carried a duplication sizing 40 Mb not involving brain-enriched genes but encompassing five lncRNAs; the latter carried a deletion sizing 1.410 Mb involving four brain-enriched genes and five lncRNAs.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, although the molecular function of PTCHD1-AS is still to be clearly elucidated, it has been demonstrated that its disruption diminished miniature excitatory postsynaptic current frequency in iPSC-derived neurons from subjects with ASD, thus supporting a role for this long noncoding RNA in the etiology of ASD (Ross et al, 2020). Interest on regulatory elements of gene expressions, like lncRNA and regulatory enhancer elements, and their involvement in brain disorders has been recently increased and new tools have been applicated for their detection, as those implicated in ASD and Schizofrenia (Piluso et al, 2019;Alinejad-Rokny et al, 2020). Deletions and duplications may overlap TDBs between two flanking topological associated domains causing a dysregulation of chromatin organization and, in turn, a dysregulation of implicated genes which ultimately affects the patient's phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focus on ID and classify ID-relevant lncRNAs based on their known, or proposed, functions ( Figure 1 ; Table 1 ) [ 55 , 68 , 107 , 108 , 109 ].…”
Section: Lncrnas In Id and Related Nddmentioning
confidence: 99%